An Analysis of Declarative Speech Act in The Movie My Lawyer, Mr Jo: Pragmatics Approach - Garda arif Wicaksono (Journal of English Language Studies, 2018)
Pragmatics is the study of how language is used in communication. Pragmatics is the study of speaker meaning. This Paper entitle “ An Analysis of Declarative Speech Act in The Movie My Lawyer, Mr Jo” discussed the analysis of speech act especially Declarative based on the Searle (1969). Speech act is a part of pragmatic that studies about utterances. It is defined as action performed via utterances(Yule,1996). Classification of Speech act (Searle:1969) are Assertives; Commisives; Expressives; Directives and Declaration. In this paper the writer focus on Declaration and analysis My Lawyer,Mr Jo. The objectives of this research were first to Undrestanding Speech act and Types of Speech act. Second, to find out of Declarative Speech act in Movie My Lawyer,Mr Jo. This research the writer use descriptive qualitative method. Keywords: Pragmatics;Speech act; Classification of Speech act; Declaration; My Lawyer, Mr Jo.